Efficacy of Transcranial Direct Current Stimulation Over Dorsolateral Prefrontal Cortex in Patients With Minimally Conscious State - Peng, Yuan; Zhao, Jingpu; Lu, Xiao; Dong, Juntao; Zhang, Shunxi; Zhang, Jin; Liu, Huihua; Zheng, Xiuyuan; Wang, Xin; Lan, Yue; Yan, Tiebin (Frontiers in Neurology, 2022)
Background: The treatment of patients in a minimally conscious state (MCS) remains challenging. Transcranial direct current stimulation (tDCS) is a noninvasive therapeutic method in treating neurologic diseases by regulating cortical excitability. The aim is to investigate the effect of tDCS in patients with MCS in this study. Methods: Eleven patients in MCS were enrolled in the study. All patients received 5 daily sessions of 20-minute sham tDCS followed by 10 sessions of 20-minute real tDCS. The anodal electrode and cathodal electrodes were placed over the left dorsolateral prefrontal cortex (DLPFC) and the right eyebrow, respectively. Assessment of Coma Recovery Scale-Revised (CRS-R) scores and resting-state functional MRI (rs-fMRI) scans were conducted three times in each patient: before tDCS (baseline, T0), post- sham tDCS at week 1 (T1), and post- real tDCS at week 2 (T2). The whole-brain functional connectivity (FC) was obtained by computing FC from six seed regions bilaterally: Precuneus, Middle frontal gyrus, Supplemental motor area, Angular gyrus, Superior temporal gyrus, and Occipital lobe. One-way repeated measure analysis of variance was used to compare the differences of CRS-R scores and FC at T0, T1, and T2. False discovery rate correction of p < 0.001 was adopted for controlling multiple comparisons in FC analysis. Results: Five patients with MCS showed obvious clinical improvement represented by increased CRS-R scores post- 2-week real tDCS. The CRS-R scores did not change post- 1-week sham treatment. No side effects were reported during the study. FC of bilateral supplementary motor area, right angular gyrus, and right superior temporal gyrus were significantly enhanced after 2-week real tDCS compare with that after 1-week sham-tDCS. In addition, FC of bilateral occipital lobe and right precuneus were significantly enhanced post- 2-week real tDCS compared with baseline. Conclusion: Our findings indicated that tDCS over DLPFC could serve as a potentially effective therapy for improving the consciousness state in patients with MCS. FC in rs-fMRI can be modulated by tDCS at both the stimulation site (left DLPFC) and the distant regions.